Blood Donors Deferral- Causes - Samina Tufail , Fatima Babar ,Nadeem Ikram , Masooma Raza ,Huma Abdul-Shakoor, (Journal of Rawalpindi Medical College, 2013)
Background: To determine the frequency and reasons of rejection of blood donors. Methods: In this descriptive study the evaluation of blood donors was carried out for jaundice,anaemia, malaria, ulcers, diabetes, syphilis, tuberculosis, rheumatic fever, cardiac or renal disease, convulsion or fainting spells, loss of weight, previous blood donations, allergy ,serious illness , surgery, blood transfusion, immunization and history of pregnancy in case of females. Results: Out of 1833 donors 249(13.58%) were rejected with 238 males and 11 females. Most common cause of deferral was anemia (4.9%), followed by HCV confirmed positive (3.1%), thrombocytopenia (1.8%) and HBsAg positive (0.81%). Permanent rejections were 34% and included HCV positive, HBsAg positive, HIV positive, diabetes and hypertension. Others were temporary deferred (66%). Conclusion: Permanent deferrals were due to hepatitis C,B,HIV, diabetes and hypertension.